2011
DOI: 10.1111/j.1651-2227.2011.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of protein catabolism in neonates and young infants post‐cardiac surgery

Abstract: Children with congenital heart disease undergoing cardiac surgery achieved anabolism with >55 kcal/kg/day and >1 g/kg/day of protein. Balance of phosphate was useful to monitor cell breakdown. Anthropometric measurements were not valuable to evaluate nutritional therapy in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Various authors have reported in postsurgical infants the use of biochemical markers (creatinine, phosphate, 3‐methylhistidine, urea, insulin‐like growth factor I, C‐reactive protein, prealbumin, etc.) to assess whether the inflammatory response to surgery has subsided and a transition from a state of catabolism to one of anabolism has occurred . Nitrogen balance remains the gold standard and should be sufficient to assess the presence of an anabolic or catabolic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported in postsurgical infants the use of biochemical markers (creatinine, phosphate, 3‐methylhistidine, urea, insulin‐like growth factor I, C‐reactive protein, prealbumin, etc.) to assess whether the inflammatory response to surgery has subsided and a transition from a state of catabolism to one of anabolism has occurred . Nitrogen balance remains the gold standard and should be sufficient to assess the presence of an anabolic or catabolic condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study from Brazil, patients became anabolic post-cardiac surgery with a calorie intake of 54 kcal/kg/day and a protein intake of 1.1 g/kg/day. 42 The decline in C-reactive protein levels to values <2 is considered an indirect marker of the onset of the anabolic phase in critically ill patients; however, its relevance in post-cardiac surgical patients has not been proven. 59 For neonates and infants, particularly in low-and middle-income countries, human breast milk is the preferred form of enteral feeding, although the practicalities of maintaining breast milk production in this context may be challenging.…”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…Because of their lower protein and energy reserves, infants and newborns may be particularly vulnerable to the hypercatabolic state that is expected following heart surgery, 41 , 42 although hypercatabolism may not follow all paediatric cardiac operations 43 . This situation is further worsened by comorbidities such as lack of protein:calorie provision or major infections (Fig 1).…”
Section: Impact Of Preoperative State On Postoperative Outcomementioning
confidence: 99%
“…A significant negative nitrogen balance has been reported in critically ill children with hypercatabolic conditions like injury, trauma, postsurgical condition, or severe sepsis 25 , 89 100 . To accurately estimate the protein status, nitrogen balance is calculated as nitrogen intake minus nitrogen losses from urine, stool, skin, and other fluids, including dialysate and thoracic or abdominal drainage 100 105 .…”
Section: Assessment Of Body Composition and Protein Turnover During Cmentioning
confidence: 99%
“…Multiple studies in infants, children, and adolescents have reported protein prescription practices and protein balance results in different clinical conditions, including neonates on extracorporeal life support, 54 , 115 surgical infants, 135 138 postsurgical repair of congenital heart disease, 92 , 97 , 116 , 139 141 children with acute kidney injury on continuous renal replacement therapy or hemodialysis, 100 , 104 , 105 , 120 and critically ill children admitted to the PICU (Table 2). 26 , 28 , 97 , 110 , 124 , 131 , 142 …”
Section: Clinical Studiesmentioning
confidence: 99%